Upaya Meningkatkan Prestasi Belajar Siswa Pada Mata Pelajaran Matematika Menggunakan Model TGT di Kelas III A SD Negeri 2 Pliken - Sari, Novita; Wiyono, Cahyo (Proceedings Series on Social Sciences & Humanities, 2025)
This research is motivated by several problems for during observations process, is that low learning achievement in mathematics study and there are students less attention during learning and disturb the learning process. Due to lack application of learning models that can accommodate for needs of students because that still used telling method so that is monotone of learning process for students. Therefore, this research purpose to determine the increase in student learning achievement in mathematics study if using the TGT learning model in class III A SD Negeri 2 Pliken. The research method or type of research used is classroom action research (CAR). Based on achieve data during the implementation of cycles I and II, the results of the study showed that there was a fairly high increase in cycle II. For increase in learning achievement in cycle I average value of 56.41 increasing to 82.83 in cycle II. The percentage of student in cycle I was 43.47% and increased to 82.61% in cycle II. Then the conclusion is learning model Teams Games Tournament (TGT) can be improve students' learning achievement in mathematics study in class III A, in addition to improving learning achievement, this TGT model make students actively in learning as well, so is that become effectively and conducively in learning process.